2023
DOI: 10.1021/acsami.3c04797
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Icing Mechanism for a Novel Slippery Aluminum Stranded Conductor

Abstract: The icing of transmission conductor seriously threatens the safe operation of power grids. Slippery lubricant-infused porous surface (SLIPS) has shown great potential for anti-icing applications. However, aluminum stranded conductors have complex surfaces, and the current SLIPSs are almost prepared and studied on small flat plates. Herein, the construction of SLIPS on the conductor was realized through anodic oxidation and the anti-icing mechanism of the slippery conductor was studied. Compared to the untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Several test methods have been reported to assess the mechanical robustness of superhydrophobic surfaces, such as sandpaper wear, tape stripping, sand erosion tests, pencil or knife scratch tests, and liquid impact tests [16,17]. Among these, the sandpaper abrasion test is the most common method for evaluating the mechanical robustness of superhydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Several test methods have been reported to assess the mechanical robustness of superhydrophobic surfaces, such as sandpaper wear, tape stripping, sand erosion tests, pencil or knife scratch tests, and liquid impact tests [16,17]. Among these, the sandpaper abrasion test is the most common method for evaluating the mechanical robustness of superhydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This could lead to close CA values. Changes in CAH values do not have recognized theoretical support [12,13]. CAH values could be connected with the larger contact areas.…”
Section: Wettability and Anti-icing Behaviorsmentioning
confidence: 99%
“…Liu et al have reported a durable anti-icing superhydrophobic anodic alumina surface [1]. Xiang et al also confirmed the anti-icing performance of anodized aluminum strands [1,12]. Therefore, further considering the anodic oxidation method to achieve precise control of the nanopore's structure can achieve the preparation of good a anti-icing Al surface for complex aluminum strands.…”
Section: Introductionmentioning
confidence: 96%